Test of distributed applications migration to Web environments - Ciolli, María Elena (2008)
This essay is based on a previous “regression” testing knowledge, black box testing and user graphic interfaces testing. Besides, due to the fact that the testing life cycle is inside the software life cycle, the suggested focus promotes existing test cases rework, as a result of traceability of the use cases to the distributed system, the unique tests automation, integration and “regression”.